2012
DOI: 10.1007/s10719-012-9427-9
|View full text |Cite
|
Sign up to set email alerts
|

The proteoglycan repertoire of lymphoid cells

Abstract: Proteoglycans have been studied to a limited extent in lymphoid cells. In this study we have investigated the expression of proteoglycans in B-cells, CD4+ T-cells, CD8+ T-cells, natural killer cells, as well as in nine different cell lines established from patients with lymphoid malignancies. Serglycin was the major proteoglycan expressed at mRNA level by the primary lymphocytes. None of the syndecans or glycpicans was detected at mRNA level in the primary lymphocytes, except for syndecan-4 in CD4+ T-cells and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 44 publications
(48 reference statements)
4
25
0
Order By: Relevance
“…The samples were incubated with biotinylated rVAR2, potential rVAR2 binding proteins were isolated using streptavidin-coated magnetic beads and identified by Mass Spectrometry (Table 2). All cell lines expressed multiple rVAR2-bound CSPGs in line with a previous study that showed that malignant lymphoid cells in general express more types of cell-associated proteoglycans than normal lymphocytes (45). Among the hits were several well-known cancer-associated CSPGs such as CD44, CD47, CD74, and APP (46-50).…”
Section: Resultssupporting
confidence: 85%
“…The samples were incubated with biotinylated rVAR2, potential rVAR2 binding proteins were isolated using streptavidin-coated magnetic beads and identified by Mass Spectrometry (Table 2). All cell lines expressed multiple rVAR2-bound CSPGs in line with a previous study that showed that malignant lymphoid cells in general express more types of cell-associated proteoglycans than normal lymphocytes (45). Among the hits were several well-known cancer-associated CSPGs such as CD44, CD47, CD74, and APP (46-50).…”
Section: Resultssupporting
confidence: 85%
“…In a recent paper , Fadnes et al . demonstrated that the intracellular proteoglycan serglycin mRNA is dominant in lymphocytes, including CD4+ T cells, CD8+ T cells, B cells and NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent paper [38], Fadnes et al demonstrated that the intracellular proteoglycan serglycin mRNA is dominant in lymphocytes, including CD4+ T cells, CD8+ T cells, B cells and NK cells. They also showed that no syndecan or glypican mRNA was detected in lymphocytes, except syndecan-4 in CD4+ and CD8+ T cells.…”
Section: Serglycin the Most Abundant Proteoglycan In Leukocytesmentioning
confidence: 99%
“…Our binding studies performed with splenocytes show that ZZOva does not bind to T-CD4 + , T-CD8 + and B-lymphocytes, but interacts with CD11c + DCs. When ZZOVA is coupled to Tat22-57S, it remains capable of DC-targeting, but also spreads to the three populations of lymphocytes with a variable efficiency that might be due to differences in HSPG expression [26]. However, spreading does not cause a major impairment of T-cell activation and the HS-ligand has beneficial effects since the amounts of ZZOvaTat22-57S and ZZOvaDTR-BD required to stimulate CD8 + and CD4 + T-cells are approximately 10 times lower than those required for ZZOva.…”
Section: Discussionmentioning
confidence: 99%